The Analysis of Influence of The Government Expenditure on Poverty in Indonesia - Miar Miar; Ahmad Yunani (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2020)
One of the roles of the government in efforts to reduce poverty is through an allocative role in developing effective budget allocation policies that can stimulate economic growth with the ultimate goal of suppressing and reducing poverty. Government expenditure is one of the fundamental government policy tools in efforts to reduce poverty. This research focuses on the effect of government expenditure on poverty in Indonesia. The data used in this study are secondary data including data on the realization of provincial government expenditure in Indonesia, the realization of economic growth that is substituted into the GRDP at the basis of Constant Prices in the provincial government in Indonesia and poverty in proxies in the form of the number of poor people obtained from BPS period in 2014-2018. The data analysis technique which is used in this study is the path analysis technique. Based on the results of the analysis, it can be concluded that in this study government expenditure variables have a significant direct effect on poverty in Indonesia. In addition to direct influence, the results of this study also show that government expenditure variables are indirectly able to influence changes in poverty reduction in Indonesia through economic growth variables